Defect-engineered white-light emission in Zn-substituted Ni1-xZnxFe2O4–rGO hybrid spinels - T. Jose Antony; K. Jagannathan (Results in Surfaces and Interfaces, 2025)
The Zn-substituted Nickel Ferrite-rGO (NiFe2O4–rGO) nanocomposites were prepared to investigate its intrinsic defect-mediated optical emission tuning without external dopants. Formation of spinel structure with lattice distortions due to cation redistribution was confirmed by P-XRD. Uniform nanoscale distribution on rGO sheets was ascertained by HRSEM. The UV–Vis diffuse reflectance analysis revealed non-linear bandgap modification with Zn content, consistent with strain-induced electronic structure modification. The PL spectra revealed broad visible emissions dominated by intrinsic defects, with Zn substitution systematically modifying intensity and recombination dynamics. The CIE chromaticity plots revealed near-white emission, particularly for intermediate Zn content. This research illustrates that precise Zn2+ substitution itself allows for structural and photoluminescent behavior control, with a defect-engineered pathway to white-light emission. Ni1-xZnxFe2O4–rGO is a cost-effective, tunable optoelectronic material system.